2019
DOI: 10.1186/s12887-019-1674-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of household air pollution due to solid fuel combustion on childhood respiratory diseases in a semi urban population in Sri Lanka

Abstract: Background Household air pollution from combustion of solid fuels for cooking and space heating is one of the most important risk factors of the global burden of disease. This study was aimed to determine the association between household air pollution due to combustion of biomass fuel in Sri Lankan households and self-reported respiratory symptoms in children under 5 years. Methods A prospective study was conducted in the Ragama Medical Officer of Health area in Sri La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 17 publications
6
25
0
4
Order By: Relevance
“…Higher odds of pneumonia were observed in underfive children whose family uses wood as a source of fuel. This result was in line with studies conducted in India [57], and Sri Lanka [58]; and with systematic reviews conducted in Low and Middle income countries [59], and Africa, China and Latin America [60]. It was also consistent with a global review conducted by Jackson et al [61].…”
Section: Discussionsupporting
confidence: 91%
“…Higher odds of pneumonia were observed in underfive children whose family uses wood as a source of fuel. This result was in line with studies conducted in India [57], and Sri Lanka [58]; and with systematic reviews conducted in Low and Middle income countries [59], and Africa, China and Latin America [60]. It was also consistent with a global review conducted by Jackson et al [61].…”
Section: Discussionsupporting
confidence: 91%
“…Higher odds of pneumonia were observed in under-ve children whose family uses wood as a source of fuel. This result was in line with studies conducted in India (52), and Sri Lanka (53); and with systematic reviews conducted in Low and Middle income countries (54), and Africa, China and Latin America (55). It was also consistent with a global review conducted by Jackson et al (56).…”
Section: Non-exclusive Breast Feedingsupporting
confidence: 91%
“…Holding children on back while cooking foods was another factor found to be signi cantly associated with pneumonia. This association might be due to the reason that cooking foods in living rooms will cause indoor air pollution and holding a child on back while cooking foods can increase the probability of inhaling smokes and food vapors (steams) which in turn will increase the risk of acquiring pneumonia by altering the structure and function of the respiratory tract (53,58).…”
Section: Non-exclusive Breast Feedingmentioning
confidence: 99%
“…Another study (Ranathunga et al, 2019) reports on the effect of firewood cooking on the respiratory illnesses of children under 5 years where simultaneous air quality measurements were also carried out. It was found that infection induced asthma was significantly higher in homes using biomass and kerosene as fuels for cooking when compared to the use of LPG for cooking.…”
Section: Health Effects Of Air Pollutionmentioning
confidence: 99%